Skeletal Site-Specific Lipid Profile and Hematopoietic Progenitors of Bone Marrow Adipose Tissue in Patients Undergoing Primary Hip Arthroplasty - Drenka Trivanović; Marko Vujačić; Aleksandra Arsić; Tamara Kukolj; Milica Rajković; Nikola Bogosavljević; Zoran Baščarević; Mirjana Maljković Ružičić; Jovana Kovačević; Aleksandra Jauković (Metabolites)
Background/Objectives: Bone marrow adipose tissue (BMAT) has been described as an important biomechanic and lipotoxic factor with negative impacts on skeletal and hematopoietic system regeneration. BMAT undergoes metabolic and cellular adaptations with age and disease, being a source of potential biomarkers. However, there is no evidence on the lipid profile and cellularity at different skeletal locations in osteoarthritis patients undergoing primary hip arthroplasty. Methods: Acetabular and femoral bone marrow (BM) and gluteofemoral subcutaneous adipose tissue (gfSAT) were obtained from matched patients undergoing hip replacement surgery. BM, BMAT, and gfSAT were explored at the levels of total lipids, fatty acids, and cells by using thin-layerand gas chromatography, ex vivo cellular assays, and flow cytometry. Results: BMAT content was significantly higher in femoral than in acetabular BM. Total lipid analyses revealed significantly lower triglyceride content in femoral than in acetabular BMAT and gfSAT. Frequencies of saturated palmitic, myristic, and stearic acids were higher in femoral than in acetabular BMAT and gfSAT. The content of CD45+CD34+ cells within femoral BMAT was higher than in acetabular BMAT or gfSAT. This was associated with a higher incidence of total clonogenic hematopoietic progenitors and late erythroid colonies CFU-E in femoral BMAT when compared to acetabular BMAT, similar to their BM counterparts. Conclusions: Collectively, our results indicate that the lipid profiles of hip bone and femoral BMAT impose significantly different microenvironments and distributions of cells with hematopoietic potential. These findings might bring forth new inputs for defining BMAT biology and setting novel directions in OA disease investigations.